Failure To Thrive In Children Under Two Years Of Age And Associated Factors, A Hospital- Based Study - M Khalil , Hassan; M Husain , Sundus; S Alkhateeb , Maghreb; I Alezzi , Jalil (Diyala Journal of Medicine, 2019)
Background: Failure to thrive is a common problem in infancy and children result from inadequate nutrition or chronic illnesses. Objective: To assess the severity and risk factors associated with failure to thrive. Patients and Methods: In this cross-section study, 50 children under 2 years of age with FTT admitted to Jalawla general hospital, Diyala province, Iraq during the period 1st of Jan. to 1st of July 2018 were studied. The parameters used to assess the growth of involved children included weight, height and head circumference for ages, using Z-score (Standard deviation score) and the mean had been taken from Tanner growth chart. Other child variables included socioeconomic status and hemoglobin level also studied. Results: The male: female ratio was 1.5:1 and 38 children (76%) were below one year of age, 25 of them (50%) were of low socioeconomic state and the majority from overcrowded families. Maternal illiteracy was recorded in 26 (52%). Twenty-three children (46%) were exclusively bottle-fed. Twenty-two children (44%) their weights for age were < -3SD below the mean, twelve children (14%) their heights for age were <-3SD, seven children (14%), had head circumference <-3SD which indicate very severe malnutrition. Most of children in this study were from large size families with low socioeconomic status. Conclusion: Failure to thrive is a common problem in our locality. Those below one year of age constitutes 76%, and 50% were from low socioeconomic families. DOI:https://doi.org/10.26505/DJM.17024770703